Mechanism of Coal Burst Triggered by Mining-Induced Fault Slip Under High-Stress Conditions: A Case Study - Bai, Jinzheng; Dou, Linming; Li, Jiazhuo; Zhou, Kunyou; Cao, Jinrong; Kan, Jiliang (Frontiers in Earth Science, 2022)
Coal burst disaster is easily triggered by mining-induced fault unloading instability involving underground engineering. The high static stress environment caused by complex geological structures increases the difficulty in predicting and alleviating such geological disasters caused by humans. At present, the mechanism of coal burst induced by mining-induced slip fault under high-stress conditions still cannot be reasonably explained. In this paper, the burst accidents occurring near mining-induced slip fault under high-stress conditions were carefully combed, the “time-space-intensity” correlation of mining, fault, syncline and anticline structure of the working areas was summarized. On this basis, the rotation characteristics of the main stress field of the fault surface subjected to mining under high-stress conditions and the evolution law of stress were analyzed. Last, based on the spectrum characteristics of burst displacement, first motion of P-wave and the ratio of Es/Ep, the source mechanism behind mining-induced fault slip under high-stress conditions was revealed. The results demonstrate that the coal burst triggered by the fault slip instability under high-stress conditions is closely related to the mining disturbance and the fold structure. Mining activities trigger the unloading and activation of the discontinuous structural surface of the fault, the rotation of the stress field and the release of a large amount of elastic strain energy and cause dynamic disasters such as coal burst. The research results of this paper are helpful to enrich the cognition of the inducing mechanism of fault coal burst.